Rapid and discriminative detection of nitro aromatic compounds with high sensitivity using two zinc MOFs synthesized through a temperature-modulated method. Issue 44 (9th October 2015) - Wan, Xiu-Yan; Jiang, Fei-Long; Liu, Cai-Ping; Zhou, Kang; Chen, Lian; Gai, Yan-Li; Yang, Yan; Hong, Mao-Chun
Abstract : Two 3D fluorescent Zn-MOFs solvothermally synthesized by a temperature-modulated method exhibit rapid and discriminative detection of nitro aromatic compounds with high sensitivity. Abstract : Two 3D MOFs (1 and2 ) have been solvothermally synthesized by introducing a π-electron conjugated fluorescent aromatic polycarboxylate ligand under the modulation of reaction temperature. Intriguingly, complex2 shows an unusual fluorescence thermochromism. Upon decreasing the temperature, the emission bands exhibit different variation behaviors which result in dramatic changes of the emission color. The fluorescence of1 and2 dispersed in DMF ( N, N -dimethylformamide) can be selectively and sensitively quenched by using nitro aromatic compounds (NACs) with a fast response time of just 10 s, indicating that1 and2 are potential real-time response candidates for detecting NACs. More interestingly, when DNP (2, 4-dinitrophenol) and PNA ( p -nitroaniline) are introduced, distinctive fluorescence signals, which can discriminate them from other NACs, are observed, making1 and2 the rare materials that can distinguish different nitro aromatic molecules.